Строение и высокотемпературная сверхпроводимость пленок Bi₂Sr₂CaCu₂Oᵧ - Samoylovich, M. I.; Belyanin, A. F.; Ilyushechkin, A. Yu. (PE "Politekhperiodika", Book and Journal Publishers, 2007)
Bi–Sr–Ca–Cu–O films exhibiting high-temperature superconductivity were fabricated on MgO{100}, LaAlO₃{100}, Al₂O₃, and Ag substrates using stencil printing and RF magnetron sputtering followed by thermal treatment near the melting temperature. The influence of fabrication parameters on the structure, composition, and superconducting properties of the films was investigated. The functionality of the obtained films at low temperatures and ultrahigh frequencies was demonstrated using fabricated microstrip resonators.